Big Data In The Public Sector : Systematic Literature Review And Bibliometric Analysis - Supriyadi, Rita Sahara; Abraham, Irfan; Giyanto, Bambang; Asropi, Asropi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to study and analyze systematically and in depth how Big Data is implemented in the public sector. The research method uses a systematic literature review and bibliometric analysis. The stages in the literature review using the PRISMA technique are identification, screening, equity and inclusion. Bibliometric Analysis is used to see research trends and their relationship with other studies. Search articles using a database of internationally reputed journals such as elsevier, springer, francis and taylor and wiley published from 2015 to 2021. Processing of bibliometric analysis using the Vos Viewer device. Based on the Publish and Perish search, 473 articles related to the research theme were generated. The results show that the application of big data in the public sector can improve the performance of government employees, increase efficiency and optimization of the bureaucracy and big data in the smallholder agricultural sector can answer the challenges of food production.